(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the rate and extent of antibiotic resistance of Escherichia coli and Klebsiella pneumoniae strains isolated at Le Van Thinh Hospital in 2023. Subjects and Methods: A retrospective study of the antibiotic susceptibility data of Escherichia coli and Klebsiella pneumoniae isolated from patients treated at Le Van Thinh Hospital from January 1, 2023, to December 31, 2023. Results: The majority of the subjects were male (50.4%), primarily over the age of 50 (80.8%). Most of the specimens were isolated from the General Surgery Department and various Internal Medicine Departments. The main types of specimens from which E.coli and K.pneumoniae were isolated included urine, swab of wound/soft tissue, and sputum. E. coli showed resistance to most cephalosporins (61.2% - 74.7%), quinolones (62.7% - 68%), and co-trimoxazole (72.7%). K. pneumoniae exhibited resistance to most cephalosporins (50% - 83.3%), quinolones (60.9% - 66.7%), co-trimoxazole (62.8%), and β-lactam combination agents (58.3% - 69.6%). Conclusion: The antibiotic resistance situation of E. coli and K. pneumoniae is increasingly complex, with significant resistance levels to various antibiotics.